Uffect Of Adding Vaname Shrimp Powder (Litopenaeus Vannamei) on Organoleptic Test in Shrimp Pudding - Setiawan, Doni (Bantara Journal of Animal Science, 2024)
Indonesia is famous for its wide variety of processed foods and very abundant food resources. One of them is pudding. Pudding is a type of dessert that is popular with many people of various ages. Pudding is in great demand because of its sweet taste and soft texture, especially with the addition of fruit or vegetables to the pudding. Apart from that, it can also be applied with the addition of vaname, which can increase the nutritional value of the pudding. The aim of this research is to determine the level of people's liking for shrimp pudding. The main treatments in this study included five treatments that varied with the addition of shrimp powder, divided into four groups: UP0 (0 gr), UP1 (10 gr), UP2 (20 gr), UP3 (30 gr), UP4 (40 gr), UP5 (50 gr). I am like a test with 60 panelists. This research design will implement a completely randomized design (CRD) with four repetitions. ANOVA statistical test was carried out to analyze the data. If there were significant differences between food treatments, it was continued with the Duncan test.